A qualitative examination of major barriers in implementation of reverse logistics within the South Australian construction sector. Issue 3 (2nd July 2016) - Rameezdeen, Raufdeen; Chileshe, Nicholas; Hosseini, M. Reza; Lehmann, Steffen
Abstract : Despite extensive research on the benefits of reverse logistics (RL), it has yet to become commonplace in the construction industry. Furthermore, the uptake and number of studies on RL remains very limited within the Australian context and particularly related to the construction industry. This paper is aimed at filling that knowledge gap by employing an exploratory approach to examine the critical barriers faced by South Australian construction organizations in implementing RL practices. Semi-structured interviews and a ranking approach facilitated the treatment of qualitative data through quantitative coding using cloud-based applications. The research identified 12 barriers to RL implementation, four of them very significant according to the responses of the interviewees: the regulatory environment, additional costs involved, lack of recognition in the construction supply chain, and extra effort required. The study also explored their inter-relationships through the Co-occurrence Index. The study proposes some remedial measures for RL implementation in South Australia based on the barriers identified.